MEMBANGUN KONEKSI DIGITAL UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA BAROS - Hilman, Mohamad; Januriana, Andi Moch; Holilah, Holilah; Sukarna, Royan Habibie (LPPM Universitas Bina Bangsa, 2024)
In today's technological advancements, every process can now be carried out digitally. Digital connectivity refers to the connection or network that enables electronic devices to communicate, exchange data, and interact through digital media. In terms of service delivery, a platform is needed that allows interaction between service providers and consumers, where interactions occur solely through mobile communication devices (smartphones). Baros Village in Warunggunung Subdistrict, Lebak Regency, Banten Province, with an area of 136 hectares and a population of 5,573 people, has the potential to become an integrated village by connecting the village community with the village government. This can be achieved by integrating participatory and collaborative elements through the development of a village website. The village website is expected to expedite the service process, improve access to information, and strengthen communication between village residents and the village government. Consequently, community participation in village development will increase, along with the realization of more effective and efficient public services